2020
DOI: 10.1177/1178632920984161
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 Pandemic in Children With Cancer: A Report From Saudi Arabia

Abstract: In January 2020, the WHO declared the novel coronavirus (2019-nCoV) outbreak as a public health emergency of international concern. Due to the rapid spread of 2019-nCoV, all countries started preventive and precautionary measures to prevent COVID-19 infection spread. These measures limited the population mobility and services provided, which subsequently Impact of on children with cancer and cancer care delivery in the many health centers in Saudi Arabia. We did a cross-sectional study to assess the impact of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
62
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(70 citation statements)
references
References 22 publications
3
62
1
4
Order By: Relevance
“…(II) Experiences of accessing cancer treatment and care services Participants in the majority of the included studies reported experiences of treatment delays [17,18,20,22,24,[25][26][27][28][29][30][31].…”
Section: Results Of Thematic Synthesismentioning
confidence: 99%
See 4 more Smart Citations
“…(II) Experiences of accessing cancer treatment and care services Participants in the majority of the included studies reported experiences of treatment delays [17,18,20,22,24,[25][26][27][28][29][30][31].…”
Section: Results Of Thematic Synthesismentioning
confidence: 99%
“…(III) Communication in relation to cancer care Disruptions in regular communications between patients and health services were commonly reported including the use of remote forms of communications using video technology or telephone [17,20,22,30,35]. Patients identi ed positive aspects of telecommunication for example, the ease of accessing care from the privacy and comfort of one's home and the ability to maintain physical distance [22].…”
Section: Results Of Thematic Synthesismentioning
confidence: 99%
See 3 more Smart Citations